Are Top Management Teams Compensated as Teams? A Structural Modeling Approach - Li, Chen (Management Science, 2024)
I develop two empirical models to quantify agency friction caused by moral hazard in top management teams. They capture shareholders’ distinct perspectives on compensating top managers: the Individual Model, in which managers in a firm unilaterally shirk, and the Team Model, in which managers choose effort jointly. The Team Model rationalizes observed compensation better than the Individual Model, underlining the importance of managerial coordination and team-based incentives. This paper also offers novel estimates of agency friction in a team production setting. Risk premium explains a large portion of the pay differential across and within firms. Firm value would have dropped between 4% and 15% if managers shirked. Additional counterfactual estimation suggests that shareholders could reduce the total compensation by up to $17 million if they were to switch from the individual perspective to the team perspective. This paper was accepted by Shivaram Rajgopal, accounting. Funding: This work was supported by the Professional Staff Congress and the City University of New York (PSC-CUNY) [Grant 67780-00 45]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2024.4982 .